Neurotechnologies in education: Assessing student engagement, attention analysis, and cognitive monitoring (Research, Society and Development, 2023)
The study aims to explore the impact of neurotechnologies in education, focusing on their application to assess engagement, analyze attention states, and monitor cognitive overload in students. The proliferation of sensors in everyday devices for monitoring physiological parameters is highlighted. Neurotechnology emerges as a valuable tool for gaining insights into cognitive processes, providing relevant metrics for student engagement, overload, and attention. The research conducts a narrative literature review, focusing on innovative opportunities to enhance teaching and learning, with an emphasis on neurotechnologies as promising instruments for understanding students' cognitive development.